P–091 Magnetic Activated Cell Sorting (MACS) improves euploid blastocysts rate in pre-implantation genetic testing cycles with high levels of sperm DNA fragmentation and advanced paternal age. (6th August 2021) - Scarselli, F; Cursio, E; Colasante, A; Zazzaro, V; Andrea, P; Gatti, S; Paccagnini, D; Uva, D; Cerquetti, C; Greco, P; Greco, A; Mencacci, C; et al.
Abstract: Study question: Can MACS increase euploid blastocyst rate in Pre-implantation Genetic Testing (PGT) cycles for AMA-APA (Advanced Maternal-Paternal Age) in patients with high sperm DNA fragmentation (SDF)? Summary answer: A slight increase in euploid blastocyst rate was found using MACS in infertile patients with high SDF undergoing PGT cycles compared to the control group. What is known already: Many authors have shown a close correlation between the presence of apoptotic markers on spermatozoa and the failure of assisted reproduction treatments. In normal physiological conditions, apoptotic spermatozoa with phosphatidylserine (PS) residues externalized on the plasma membrane, are eliminated along female genital tract, preventing oocyte fertilization. MACS eliminates apoptotic sperm whit PS residues using superparamagnetic microbeads conjugated with annexin V. This technique reduces the proportion of sperm with high rates of SDF and can be used to maximize ART procedures results. MACS application improves sperm quality, fertilization, cleavage and pregnancy rates reducing miscarriage rate. Study design, size, duration: From June to November 2020, 10 couples in which MACS was applied to select non-apoptotic spermatozoa, were randomly enrolled in our study (MACS group) and 8 couples without MACS were considered as controls (No-MACS Group). All couples in both groups underwent a PGT cycle and had high sperm DNA Fragmentation (> 20%). A higher rate of euploid and diploid-euploid mosaic blastocysts were obtained in the MACS group compared to the control group. Participants/materials, setting, methods: Patients with severe oligoastenoteratozoospermia were excluded. MACS protocol was performed as follows: semen sample was analyzed (WHO 2010) and washed with buffered medium; pellet was removed and a swim-up was performed. Retrieved spermatozoa were washed with a binding buffer (Miltenyi Biotec), centrifuged (400 g x 4 minutes) and supernatant discarded. Pellet was covered with Annexin-V and re-suspended. After 15 minutes incubation at room temperature, the sample was eluted through the column and collected for ICSI. Main results and the role of chance: In MACS group, female and male mean age ± SD were 41.6 ± 2.1 and 43.5 ± 7.3, respectively. Female and male mean age ± SD were 41.7 ± 2.8 and 44.6 ± 8.1 in the No-MACS group, respectively. In MACS and No-MACS groups, injected oocytes were 44 and 35, fertilized oocytes were 32 (72.3%) and 27 (77.1%) (NS), blastocyst formation rates were 71.8% (23/32) and 48.1% (13/27) (NS), respectively. In No-MACS group, only 1 euploid and 1 diploid-euploid mosaic blastocysts were obtained (1/13 = 8%) (NS). In MACS group, 4 euploid blastocysts were formed (4/23 = 17.4%) whereas mosaic diploid-euploid blastocysts were 3/23 (13.0%) (NS). Aneuploid blastocysts were 16/23 (69.6%) in MACS group and 11/13 (84.6%) in No-MACS group (NS). Limitations, reasons for caution: AMA and APA of couples enrolled should be considered as a limit of the study. A larger number of patients and biopsied blastocysts are needed to analyze clinical results and perform a robust statistical analysis establishing if MACS is useful to improve transferable blastocyst rate in patients with high SDF. Wider implications of the findings: MACS is useful to select non apoptotic sperms; although fertilization, cleavage and blastocyst rates are not improved, aneuploid blastocysts rate slightly decreases using MACS. It I possible that, selecting spermatozoa free from PS residues, MACS allows to choose spermatozoa with a better DNA packaging, thus affecting the embryo ploidy. Trial registration number: non applicable